CNAC (Conseil National des arts culinaires): Provence-Alpes-Cote d'Azur; Midi-Pyrenees; Corse; Martinique; Acquitaine; Languedoc-Roussillon; Lorraine; Guadeloupe; Limousin; Alsace; Picardie; Guyane - Davidson, Alan E (Petits Propos Culinaires, 1999)
CNAC (Conseil National des arts culinaires): Provence-Alpes-Cote d'Azur; Midi-Pyrenees; Corse; Martinique; Acquitaine; Languedoc-Roussillon; Lorraine; Guadeloupe; Limousin; Alsace; Picardie; Guyane: the latest volumes in the series 'L'inventaire du patrimoine culinaire de Ia France': CNAC/Aibin Michel, Paris, 1998, 1999: ISBN numbers all begin with 2-226 ... : several hundred pages each, bibliographical material supplied, indexes. This extended essay reviews the latest volume on Guyane.